Imaging diagnosis for intervertebral disc. Issue 1 (29th September 2019) - Ogon, Izaya; Takebayashi, Tsuneo; Takashima, Hiroyuki; Morita, Tomonori; Terashima, Yoshinori; Yoshimoto, Mitsunori; Yamashita, Toshihiko
Abstract: Various functional magnetic resonance imaging (MRI) techniques have been investigated in recent years and are being used in clinical practice for the patients with low back pain (LBP). MRI is an important modality for diagnosing intervertebral disc (IVD) degeneration. In recent years, there have been several reported attempts to use MRI T2 mapping and MRI T1ρ mapping to quantify lumbar disc degeneration. MRI T2 mapping involves digitizing water content, proteoglycan content, and collagen sequence breakdown as relaxation times (T2 values) at each site. These digitized values are used to create a map, that is, then used to quantitatively evaluate the metabolite concentrations within IVD tissues. MRI T2 mapping utilizes the T2 relaxation time to quantify moisture content and the collagen sequence breakdown. MRI T1ρ mapping digitizes water molecule dispersion within the cartilaginous matrix to evaluate the degree of cartilaginous degeneration. Magnetic resonance spectroscopy is a less‐invasive diagnostic test that provides biochemical information. Adequate analysis of the IVD has not yet been performed, although there are indications of a relationship between the adipose content of the multifidus muscle in the low back and LBP. The ultra short TE technique has been recently used to investigate lumbar cartilaginous endplates. Unlike diagnosis based on contrast‐enhanced images of the IVD, which depends on the recurrence of pain that is determined subjectively, MRI‐based diagnosis is less‐invasive and based on objective imaging findings. It is therefore expected to play a key role in the diagnostic imaging of IVD conditions in the future. Abstract : Rapid advances in the qualitative diagnosis of IVD disorders using MRI have been made in recent years. Several reports have described the identification of the injury site using various imaging techniques and its relationship to pain. As an alternative to diagnosis based on IVD contrast‐enhanced images, which depends on the recurrence of pain that is expressed subjectively, MRI‐based diagnosis is less‐invasive and based on objective imaging findings, and it is therefore expected to play a more central role in the diagnostic imaging of IVD conditions in the future.